Formulation of a peach ice cream as potential symbiotic food - VILLALVA,Fernando Josué (2017)
Abstract Today’s population increasingly demands and consumes healthy products. For this reason, the food industry has been developing and marketing food with added bioactive components. The aim of this work was to formulate a peach ice cream reduced in calories with an added probiotic (Bifidobacterium lactis Bb-12) and prebiotics (inulin), and to evaluate its sensory quality and acceptability as potential symbiotic food. The moisture content was 76.47%; 7.14% protein; 0.15% fat; 6.37%; carbohydrates; 9.87% inulin; 1.22% ash; 0.201% calcium, 0.155% phosphorus and 0.168% sodium. On the first and 21th day of storage counts of B. lactis Bb – 12 was 4 x 108 CFU/mL and 1.5 x 107 CFU/mL, respectively. It was possible to formulate a peach ice cream reduced in calories, fat, and sugar and with potential symbiotic effect, by addition of B. lactis Bb – 12. A product with suitable organoleptic characteristics, creamy texture, peachy colour, taste and flavour, and no ice crystals was obtained. This ice cream would be a suitable food matrix to incorporate prebiotic and probiotic ingredients as a potential symbiotic food.